Pain in Neonates: A Concept Analysis - Fitri, Siti Yuyun Rahayu (Anesth Pain Med, 2019)
CONTEXT: The term pain in neonates is emerged in recent decades. However, studies on pain in neonates are still limited and have various indicators. In addition, the term pain still often overlaps with stress in various studies and clinical circumstances. The concepts of pain and stress in the neonates need to be clarified to be better understood and then applied to improve neonates’ quality of life. Therefore, the current study aimed at clarifying the concept of pain in neonates. EVIDENCE ACQUISITION: The current study employed the concept analysis approach developed by Walker and Avant. The authors reviewed articles from JSTOR, ScienceDirect, Proquest, Sage, Cochrane, and Springer databases from 1980 to 2016 using keywords pain, stress, neonatal, neonates, and quality of life. RESULTS: Pain had attributes such as tissue damage, physiological changes, metabolic changes, and behavioral changes. Stress had attributes such as physiological changes, metabolic changes, and behavioral changes. CONCLUSIONS: Attributes of pain and stress have similarities and differences. The main difference is the stimulus that induces a response. Pain has an attribute of tissue damage, whereas stress is not always due to tissue damage. The attributes of physical, metabolic, and behavioral changes between pain and stress are similar.